Child Abuse In Gabrielle Tallent's My Absolute Darling - Wibowo, Lintang; Litaay, Adeline Grace Marianne (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
This study discusses about child abuse that is experienced by Julia “Turtle Alveston in Gabrielle Tallent’s My Absolute Darling. This study tells about the abuse that is experienced by Turtle, the main character. This study aims to reveal three points: the kinds of child abuse, the causes of child abuse, and the effects of child abuse of that happen to Turtle Alveston. This study uses the psychological approach of literature as it helps to find out how Turtle experiences the abuse that is done by her father, Martin. Gabrielle Tallent’s My Absolute Darling is used as the source of the data. Some quotations are added to support the analysis. As the results, the writer finds that the cause of the abuse is family dynamics as a pivotal factors in perpetuating child abuse. Also, the kinds of abuse found are psychical abuse, emotional abuse, psychological abuse, verbal abuse, coercive control, intimidation and threats, and sexual abuse. Last but not the least, the effects of the abuse are psychological and emotional trauma, social dysfunction, and physical health issues and behavioral problem